Are Ethical Responses Linked to Locus of Control? - Smith, Aileen (Teaching business ethics, 1998)
Locus of control (LOC) has received considerable attention in the psychological literature. However, there is limited research and inconclusive results reported from the research examining its potential relationship to ethical beliefs and attitudes., This research examines how the locus of control of university students (n = 671) can be linked to their ethical responses concerning academic-behavior items. Whenever the students were asked about their personal beliefs concerning the unethical nature of academic-environment behaviors, the results indicated significant differences (α ≤ 0.05) by the internal/external LOC designation on 21 of the 27 items. Because a review of the literature indicated that there might be an interaction of LOC scores, gender, and age, an analysis of variance was performed. An ANOVA was used to analyze the ethical responses using a 3-level age classification (AGECLASS) variable and a 4-level LOC/GENDER variable (INTMale, EXTMale, INTFemale, EXTFemale). Overall results indicated both AGECLASS and LOC/GENDER variables to be significant on the survey responses.